Indicaciones y contraindicaciones de la cirugía endodóntica (1994)
ABSTRACT: This article is a review and rationalization of the indications and contraindications of endodontic Surgery. The first option to solve an endodontic failure is retreatment; once this possibility is discarded, surgery would be the treatment of choice.